2022
DOI: 10.3390/pathogens11091026
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Glycosyltransferase RsIA_GT of Rhizoctonia solani AG-1 IA Inhibits Defense Responses in Nicotiana benthamiana

Abstract: Anastomosis group AG-1 IA of Rhizoctonia solani Khün has a wide host range and threatens crop production. Various glycosyltransferases secreted by phytopathogenic fungi play an essential role in pathogenicity. Previously, we identified a glycosyltransferase RsIA_GT (AG11A_09161) as a secreted protein-encoding gene of R. solani AG-1 IA, whose expression levels increased during infection in rice. In this study, we further characterized the virulence function of RsIA_GT. It is conserved not only in Basidiomycota,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…In general, effectors share the common property of inducing or inhibiting cell death in plants (Bos et al., 2006; Chen et al., 2021; Sharpee et al., 2017; Wei et al., 2020; Zhang et al., 2022). We have previously reported that the purified recombinant RsIA_CtaG/Cox11 could induce disease‐like symptoms when infiltrated into rice leaves (Zheng et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, effectors share the common property of inducing or inhibiting cell death in plants (Bos et al., 2006; Chen et al., 2021; Sharpee et al., 2017; Wei et al., 2020; Zhang et al., 2022). We have previously reported that the purified recombinant RsIA_CtaG/Cox11 could induce disease‐like symptoms when infiltrated into rice leaves (Zheng et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Since the beginning of the draft genome analysis of R. solani AG‐1 IA, we have characterized several candidate effectors (Niu et al., 2023; Wei et al., 2020; Xia et al., 2017; Zhang et al., 2022; Zheng et al., 2013). RsIA_CtaG/Cox11 is one of the first effector candidates to be experimentally verified, but our previous results were limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expanded and contracted families of this species also showed enrichment in the transporters 2.A.1 (Major Facilitator Superfamily, P = 1.87e-58, Fisher’s Exact Test), which, among other roles, have been involved in resistance to oxidative stress and fungicides in some pathogenic fungi (49, 50). Lastly, the expanded and contracted families in N. parvum are enriched in glycosyltransferases (GT1_153) ( P = 1.08e-16, Fisher’s Exact Test, Supplementary figure 9), which have been associated with virulence in some pathogenic fungi (51, 52).…”
Section: Resultsmentioning
confidence: 99%
“…As an HR-like stimulator, Bax is important for the study of effector immune function ( 52 ). When used as an activator, Bax is an important factor for screening whether the pathogen effector inhibits the immune response ( 40 , 52 , 53 ). Therefore, Bax can be used as a convenient elicitor to screen the functional domains of immunosuppressive effectors of phytoplasmas that cannot be cultured in vitro .…”
Section: Discussionmentioning
confidence: 99%